Memória institucional do IBGE: um estudo exploratório-metodológico - Costa, Icléia Thiesen Magalhães (1992)
A methodological-exploratory study on institucional historical records is developed, taking as a reference point the IBGE Institucional Historial Record. Its general aim is the construction of methodological and theoretical parameters based on results derived from the survey, in order to widen the existing information on the subject. Those parameters constitute a preliminary ground for the planing of the Retrieval System for the IBGE Institucional Historical Record, for purposes of preserving it. The study is designed more specifically to contribute to the improvement of data collection and analysis techniques, by reporting right and wrong directions taken on the away.